Local Regulation of the Mayor of Kendari City Number 19 of 2014 on HIV and AIDS Response: A SOAR Analysis Approach - Muh.Fajrinshadiq Rusli; Harniati Harniati; Annisa Qoriyah Nur (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: HIV/AIDS remains a significant global public health concern, including in Kendari City, where reported cases continue to rise. In response to this growing challenge, the Kendari City Government enacted Local Regulation No. 19 of 2014 concerning HIV and AIDS Response. This regulation aims to curb the transmission of HIV, enhance the quality of life of people living with HIV/AIDS (PLWHA), and eliminate stigma and discrimination. Objective: This study aims to evaluate the effectiveness of Local Regulation Number 19 of 2014 in preventing and controlling HIV/AIDS in Kendari City using the SOAR (Strengths, Opportunities, Aspirations, Results) analytical framework. Methods: This research employed a qualitative descriptive design through the analysis of policy documents and supporting literature. The SOAR framework was applied to identify internal strengths, external opportunities, shared aspirations, and the resulting outcomes of the policy. Results: The regulation demonstrates several strengths, including a solid legal foundation, a non-discriminatory approach, and multisectoral collaboration. Opportunities identified include expanded access to health services, increased public awareness, and greater budgetary support. Policy objectives target reducing HIV prevalence, enhancing institutional capacity, and improving the wellbeing of PLWHA. Conclusion: Local Regulation No. 19/2014 represents a strategic initiative in the local response to HIV/AIDS. Its success, however, depends on sustained collaboration among government institutions, civil society, and the private sector to ensure effective implementation and long-term impact on public health outcomes. Keywords: Local Regulation, HIV/AIDS, SOAR Analysis, Public Health Policy, Kendari City